The letters of John - Watson, Duane Frederick 1956- (Cambridge New York, NY Port Melbourne New Delhi Singapore Cambridge University Press, 2024)
"This volume provides a new commentary on the Letters of John, demonstrating how a biblical author uses contemporary rhetoric to persuade his audience to believe and behave as he deems advantageous. It explores Johannine literature, rhetorical analysis, the social world of early Christianity, and hermeneutics"--
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Commentaries; Kommentar